Study of the Accessibility of Zeolite Crystals in Polyimide Matrices. A Route to Coatings Exhibiting Selective Permeation - Marie Šnáblová Fryčová; Milan Kočiřík; Arlette Zikánová; Petr Sysel; Bohumil Bernauer; Vladislav Krystl; Ivan Hüttel; Jiri Hradil; Mladen Eić (Adsorption Science & Technology, 2005)
The accessibility of void space in MFI-type zeolite crystals, isolated and embedded in a polyimide (PI) matrix, was studied using optical microscopy coupled with an iodine indicator technique (IIT). IIT was used to estimate the adhesion between the PI matrix and the zeolitic phase, the accessibility of the zeolite void space for gas molecules as well as for characterizing the spatial distribution of embedded crystals in the composite. The channel system of the zeolitic phase in as-synthesized composites with the majority of crystals covered by a layer of PI is occupied by the solvent molecules used in composite synthesis. In untreated composites, the zeolitic phase is inaccessible to iodine sorption. Colouring patterns and colouring kinetics have been used to characterize the efficiency of the treatment for removing the PI covering layer from the crystal surface. The same techniques can be applied to characterize the treatment with regard to the desorption of solvents ( N- methyl-2-pyrrolidone, N,N -dimethylformamide, n-heptane) from the silicalite-1 channel system.